Seroprevalence and risk factors of Q fever in an indigenous community in the Brazilian Legal Amazonia (Revista de Ciência Veterinária e Saúde Pública, 2022)
Introduction: Q fever is a zoonosis caused by Coxiella burnetii, strictly intracellular and gram-negative bacteria. Humans are usually infected by contaminated aerosols from domestic animals, particularly after contact with parturient females and their birth products. Objective: To verify the seroprevalence and the risk factors for Q fever in the indigenous people living in demarcated territory in the Brazilian Legal Amazonia of Mato Grosso. Methods: 73 paired serum samples were collected from indigenous in the cohorts held in 2014 and 2015 in nine villages and serological tests were performed using the indirect immunofluorescence test to detect anti-C. burnetii IgG. Conclusions: There was a predominance of indigenous women (65.75%), aged 20 to 39 years (39.73%), occupational activity aimed at taking care of the home, family, collection in the Cerrado and cultural activities (35.61%). For associated risk factors, the handling of dry straw (50.68%) prevailed in 2014 and body contact and / or tick infestation (56.16%) in 2015. There was no serological evidence for Q fever between Haliti-Paresí in the biennium analysed and symptomatology compatible with this zoonosis, reflecting the collective engagement of health surveillance actions redirected to health action. Even though the risk factors for Q fever are related to the social determinants of the daily life, culture and environment of the indigenous people, this study considers that the low infection among the host animals of this region may have limited the accidental contact of the indigenous people and their infection.